2011
DOI: 10.1186/1755-1536-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase recruits mesenchymal-like cells to the lung and ameliorates fibrosis

Abstract: Hyaluronidases (HYALs) comprise a group of enzymes that degrade hyaluronic acid (HA). In this report, we reveal that a single intranasal inoculation of HYAL induces an increase in mononuclear cells within the bronchoalveolar space demonstrating a mesenchymal-like phenotype, expressing stem cell antigen-1 (SCA-1), CD44 and CD73 but not CD34, CD45, CD3, CD4, CD8 or CD19. This influx of mesenchymal stem cell (MSC)-like cells was dependent on leukotriene production within the lung parenchyma. These findings prompt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 43 publications
0
37
0
2
Order By: Relevance
“…Cell culture data have suggested that the loss of the defining differentiation potential of MSCs occurs in a hierarchical manner, whereby the ability for adipogenic differentiation is commonly abolished first prior to the loss of the chondrogenic differentiation potential, finally giving rise to osteogenic precursor cells4243. The observed reduction in the differentiation potential of MSCs may bear therapeutic significance, as previous publications have reported regenerative effects of mobilized endogenous MSCs in bleomycin-induced pulmonary fibrosis4445. In these datasets, pulmonary damage was mostly induced by topical intratracheal instillation of bleomycin, thereby preserving MSCs of other tissues46.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture data have suggested that the loss of the defining differentiation potential of MSCs occurs in a hierarchical manner, whereby the ability for adipogenic differentiation is commonly abolished first prior to the loss of the chondrogenic differentiation potential, finally giving rise to osteogenic precursor cells4243. The observed reduction in the differentiation potential of MSCs may bear therapeutic significance, as previous publications have reported regenerative effects of mobilized endogenous MSCs in bleomycin-induced pulmonary fibrosis4445. In these datasets, pulmonary damage was mostly induced by topical intratracheal instillation of bleomycin, thereby preserving MSCs of other tissues46.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine (CC motif) ligand 2/monocyte chemotactic protein-1 (CCL2/MCP-1) is involved in inflammatory lung disorders and can recruit leukocytes, stimulate histamine or leukotriene release from mast cells or basophils, and induce the fibroblast production of TGF-b1 and procollagen, with enhanced Th2 polarization (67). Hyaluronidases (HYALs) comprise a group of enzymes that degrade hyaluronic acid (HA), and with the HYAL treatment, TGF-b1 production and collagen deposition are decreased in bleomycin-induced lung injury while fibrosis is potently blocked (68). In airway epithelial, Src homology 2 protein tyrosine phosphatase (SHP2), a modulator of TGFb1 production, appears to modulate the TGF-b1 activity and in turn regulate allergic airway remodeling after allergen provocation in mouse models (69).…”
Section: Other Pathwaysmentioning
confidence: 99%
“…The observed changes in MRI signals might not have represented a therapeutic response in the mouse study, since no effect of hyaluronidase and budesonide on collagen or hydroxyproline could be observed by postmortem analyses, but it indicates that the BLM-elicited MRI signals can be modulated by hyaluronidase. Beginning the hyaluronidase treatment at an earlier timepoint after BLM, when collagen was still being deposited, as was the case in another study testing the enzyme in the murine BLM model (28), and/or by increasing the hyaluronidase dose might have resulted in an effect on collagen itself. Further investigations to explore possible therapeutic effects of hyaluronidase in the small rodent BLM models are warranted, and the herein reported signal changes provide a good basis for them.…”
Section: Discussionmentioning
confidence: 98%